Role of CBCT in diagnosing periodontal disease: a literature review - Arifin, Sariyani Pancasari Audry; Beatrice, Christina; Meidianti, Dwi Harini Endah (Ikatan Radiologi Kedokteran Gigi Indonesia, 2025)
Objectives: This review article aims to provide scientific information regarding the role of CBCT in diagnosing periodontal disease. Review: This literature review was conducted using an electronic database search method via Google Scholar. The keywords used were 'CBCT related to periodontal disease’. The inclusion criteria included journal articles published between 2019 and 2024. Articles were selected and filtered based on publication year, relevance to the topic, and research quality, resulting in 10 journal articles used in this review. Periodontal disease is described as an inflammatory condition affecting both soft and hard periodontal structures. It typically began as gingivitis, a mild and self-limiting inflammation. Intraoral radiographs, such as periapical and bitewing images, were the most commonly used tools for periodontal assessment, offering clear visualization of teeth, alveolar bone, and periodontal ligament space with minimal radiation exposure. However, intraoral radiographs have limitations, including difficulty visualizing bucco-lingual bone loss and a tendency to underestimate early-stage alveolar bone resorption. CBCT revealed bony abnormalities that might have been overlooked in routine clinical and radiographic assessments. Nevertheless, evidence supporting its ability to improve short- and long-term periodontal treatment outcomes remained limited. Conclusion: CBCT played a crucial role in diagnosing periodontal disease by providing superior three-dimensional imaging compared to conventional radiographs. However, its limitations included potential overestimation or underestimation of bone thickness due to voxel size, artifacts, and soft tissue overlap. Additionally, its higher radiation dose required careful clinical consideration.